Ascites Physiopathology, Treatment, Complications and Prognosis - Rodrigo, Luis (IntechOpen, 2017)
The term "ascites" is from the Greek word askites meaning "baglike." Although most commonly due to cirrhosis, severe liver disease or metastatic cancer, its presence can be a sign of other significant medical problems, such as Budd-Chiari syndrome. Diagnosis of the cause is usually done with blood tests, an ultrasound scan of the abdomen, and direct removal of the fluid by a needle or paracentesis (which may also be therapeutic). Treatment using medications (diuretics), external drainage, or other treatments is clearly defined. In this book, the authors describe the physiopathology of the diverse causes of ascites,the types of treatments recommended, the recent advances achieved, the complications and the prognosis of the different clinical situations that doctors must face.